2019
DOI: 10.1158/1055-9965.epi-18-1285
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Fibrinogen and sP-Selectin are Associated with the Risk of Lung Cancer in a Prospective Study

Abstract: Background: While enhanced platelet activation and a procoagulant state may drive lung cancer progression and metastases, less is known about their role in earlier phases of cancer development. Thus, we evaluated whether prediagnostic biomarkers of platelet activation and coagulation are related to the risk of lung cancer in the prospective EPIC-Heidelberg Study using a case-cohort design. Methods: Levels of fibrinogen, soluble glycoprotein (sGP) IIb/IIIa, soluble P-selectin (sP-selectin), soluble thrombomodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Among the coagulation factors, fibrinogen attracts much research attention because it induces inflammatory reactions and plays a vital role in tumorigenesis and metastasis. Findings of recent studies revealed that the increase of preoperative fibrinogen leads to treatment failure or poor prognosis in many kinds of tumors, such as lung cancer (19), digestive cancers (20), and solid tumors (21). A recently published study reported that elevated preoperative fibrinogen is linked to a high risk of recurrence and poor long-term prognosis in GISTs patients (22).…”
Section: Introductionmentioning
confidence: 99%
“…Among the coagulation factors, fibrinogen attracts much research attention because it induces inflammatory reactions and plays a vital role in tumorigenesis and metastasis. Findings of recent studies revealed that the increase of preoperative fibrinogen leads to treatment failure or poor prognosis in many kinds of tumors, such as lung cancer (19), digestive cancers (20), and solid tumors (21). A recently published study reported that elevated preoperative fibrinogen is linked to a high risk of recurrence and poor long-term prognosis in GISTs patients (22).…”
Section: Introductionmentioning
confidence: 99%
“…CD62P is mainly present in platelet α-particles and is an important marker for platelet activation [29]. A prospective cohort study confirmed that platelet activation was significantly associated with the lung cancer risk by the multivariate Cox regression model and that CD62P is an independent risk factor for lung cancer [30]. Flow cytometric analysis indicated that the expression of CD62P was increased in the control group compared with the normal group, and the expression of CD62P in HYW and aspirin groups was lower than the control group, suggesting that HYW and aspirin intervention can inhibit platelet activation to varying degrees.…”
Section: Discussionmentioning
confidence: 93%
“…Fibrinogen: The main substrate for coagulation in vivo. Levels of fibrinogen have been associated to the prospective risk of developing lung cancer, survival in patients with lung cancer and with metastasis in experimental models of lung cancer [19,20,24]. C-reactive protein (CRP): An acute-phase plasma protein that is elevated in systemic inflammation and is commonly used as an inflammatory marker.…”
Section: Appendix Amentioning
confidence: 99%
“…Further, the haemostatic system has been demonstrated to be involved in angiogenesis, tumour growth and metastatic spread in experimental models of lung cancer [18,19]. More recently, elevated biomarkers of haemostasis (plasma fibrinogen and soluble (s)P-selectin) have been associated with risk of lung cancer in a prospective observational study, underpinning this complex interrelation [20]. Haemostatic biomarkers and tests, such as prothrombin time, fibrinogen and D-dimer levels have further been reported to be associated with survival in patients with lung cancer [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%